Lattice-Based Robust Distributed Source Coding for Three Correlated Sources - Dumitrescu, Sorina; Elzouki, Dania; Chen, Jun (IEEE transactions on communications, 2020)
The problem of robust distributed source coding for three correlated sources is studied in this work. A lattice-based scheme is proposed and the analysis of its performance is provided in the high resolution regime. Special attention is paid to the degenerate case where the three sources are Gaussian and identical. In this case, our scheme is shown to achieve within an asymptotic gap of 0.069 bits in terms of rate per description from the information-theoretic limit of quadratic symmetric Gaussian multiple description coding with central and individual decoders, when the side distortion and the ratio between the central and side distortions both approach 0.